Morphological and histopathological heart changes in autopsies of heroin abusers - Aleksić, Ivan; Marinković, Nadica; Džambas, Jelena (Vojnosanitetski pregled, 2021)
Backround/Aim. Heroin is a semisynthetic opioid that may cause morphological and histopathological changes in heart: ventricular hypertrophy, myocardial fibrosis, hypertrophy of cardiomyocytes, myofibrils contraction band necrosis, loss of myocytes nuclei and cross-striation, perivascular bleeding, inflammatory cells infiltrate. The aim of the study was to show morphological and histopathological heart changes in autopsies of the long-time heroin abusers with positive toxicological analysis for 6-monoacetylmorphine (6-MAM) and morphine in blood and urine. Methods. Retrospective study was done at the Institute of Pathology and Forensic of the Medicine Military Medical Academy in Belgrade between 2010 and 2014 and included forensic autopsies of 27 examinees aged between 18 and 60. Heart ventricles thicknesses was analysed and histopathological myocard findings from processed material stained by hematoxyline-eosine (H&E) and trichrome stains (Masson) were examined. 6-MAM and morphine concentration in blood and urine using high-performance liquid chromatography coupled with photodiode (HPLC-PDA) and ultraviolet (UV) detector were analysed. Results. Heart ventricles thickness was increased in all persons (27/27; 100%) left 1.74 ± 0.17 cm and right 0.6 ± 0.09 cm. Myocardial fibrosis affected 27/27 (100%) of the examined persons including perivascular one in 24/27 (88.89%) and interstitial focal fibrosis in 3/27 (11.11%); hypertrophy of cardiomyocytes was present in 22/27 (81.48%); myofibril contraction band necrosis in 22/27 (81.48%); loss of myocytes nuclei and cross-striation in 10/27 (37.04%); fresh perivascular bleeding in 23/27 (85.19%); focal inflammatory cells infiltrate in 14/27 (51.85%). In toxicological findings, in 27/27 (100%), 6-MAM and morphine were found in urine. Both 6-MAM and morphine in blood were found in 3/27 (11.11%) and only morphine in blood in 16/27 (59.26%) persons subjected to an autopsy. Conclusion. Our results indicate both morphological (left and right ventricle hypertrophy) and histopathological heart changes (myocardial fibrosis, hypertrophy of cardiomyocytes, contraction-band necrosis, loss of myocytes nuclei and cross-striation, fresh perivascular bleeding and focal inflammatory infiltrate) in long-term heroin obusers. These changes are non-specific and could be caused either by long-term heroin abuse or by other factors. Having in mind a lack of medical histories of examined we could not exclude other factors besides long-term heroin abuse as cause of heart changes.
Keywords: heroin dependence; heart; myocardium; morphine; histological techniques; autopsy.